Find solutions to your problems with the help of IDNLearn.com's knowledgeable users. Join our community to receive prompt and reliable responses to your questions from knowledgeable professionals.
Sagot :
To determine which parametric equations represent [tex]\( y = -|x| \)[/tex], we need to examine each pair of parametric equations given and verify if they satisfy this relationship. Let’s analyze each one step by step.
1. Equation Pair: [tex]\( x = -t \)[/tex] and [tex]\( y = | -t | \)[/tex]
- Substitute [tex]\( x = -t \)[/tex] into [tex]\( y = | -t | \)[/tex]:
[tex]\[ y = | -t | = | x | \][/tex]
- Since [tex]\( y = | x | \)[/tex], this does not satisfy [tex]\( y = -| x | \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
2. Equation Pair: [tex]\( x = t^2 \)[/tex] and [tex]\( y = -| t^2 | \)[/tex]
- Substitute [tex]\( x = t^2 \)[/tex] into [tex]\( y = -| t^2 | \)[/tex]:
[tex]\[ y = -| t^2 | = -| x | \text{ (since \( t^2 \geq 0 \) for all real \( t \))} \][/tex]
- This satisfies [tex]\( y = -|x| \)[/tex]. Thus, this pair represents [tex]\( y = -|x| \)[/tex].
3. Equation Pair: [tex]\( x = 2t \)[/tex] and [tex]\( y = -| 2t | \)[/tex]
- Substitute [tex]\( x = 2t \)[/tex] into [tex]\( y = -| 2t | \)[/tex]:
[tex]\[ y = -| 2t | = -| 2x | = -2|x| \][/tex]
- However, [tex]\( y = -| 2x | \neq -| x | \)[/tex]. This does not satisfy [tex]\( y = -|x| \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
4. Equation Pair: [tex]\( x = t^3 \)[/tex] and [tex]\( y = | t^3 | \)[/tex]
- Substitute [tex]\( x = t^3 \)[/tex] into [tex]\( y = | t^3 | \)[/tex]:
[tex]\[ y = | t^3 | = | x | \][/tex]
- Since [tex]\( y = | x | \)[/tex], this does not satisfy [tex]\( y = -| x | \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
5. Equation Pair: [tex]\( x = t + 4 \)[/tex] and [tex]\( y = -| t + 4 | \)[/tex]
- Substitute [tex]\( x = t + 4 \)[/tex] into [tex]\( y = -| t + 4 | \)[/tex]:
[tex]\[ y = -| t + 4 | = -| x | \][/tex]
- This satisfies [tex]\( y = -|x| \)[/tex]. Thus, this pair represents [tex]\( y = -|x| \)[/tex].
In conclusion, the parametric equations that represent [tex]\( y = -| x | \)[/tex] are:
- [tex]\( x = t^2 \)[/tex] and [tex]\( y = -| t^2 | \)[/tex]
- [tex]\( x = t + 4 \)[/tex] and [tex]\( y = -| t + 4 | \)[/tex]
1. Equation Pair: [tex]\( x = -t \)[/tex] and [tex]\( y = | -t | \)[/tex]
- Substitute [tex]\( x = -t \)[/tex] into [tex]\( y = | -t | \)[/tex]:
[tex]\[ y = | -t | = | x | \][/tex]
- Since [tex]\( y = | x | \)[/tex], this does not satisfy [tex]\( y = -| x | \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
2. Equation Pair: [tex]\( x = t^2 \)[/tex] and [tex]\( y = -| t^2 | \)[/tex]
- Substitute [tex]\( x = t^2 \)[/tex] into [tex]\( y = -| t^2 | \)[/tex]:
[tex]\[ y = -| t^2 | = -| x | \text{ (since \( t^2 \geq 0 \) for all real \( t \))} \][/tex]
- This satisfies [tex]\( y = -|x| \)[/tex]. Thus, this pair represents [tex]\( y = -|x| \)[/tex].
3. Equation Pair: [tex]\( x = 2t \)[/tex] and [tex]\( y = -| 2t | \)[/tex]
- Substitute [tex]\( x = 2t \)[/tex] into [tex]\( y = -| 2t | \)[/tex]:
[tex]\[ y = -| 2t | = -| 2x | = -2|x| \][/tex]
- However, [tex]\( y = -| 2x | \neq -| x | \)[/tex]. This does not satisfy [tex]\( y = -|x| \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
4. Equation Pair: [tex]\( x = t^3 \)[/tex] and [tex]\( y = | t^3 | \)[/tex]
- Substitute [tex]\( x = t^3 \)[/tex] into [tex]\( y = | t^3 | \)[/tex]:
[tex]\[ y = | t^3 | = | x | \][/tex]
- Since [tex]\( y = | x | \)[/tex], this does not satisfy [tex]\( y = -| x | \)[/tex]. Thus, this pair does not represent [tex]\( y = -|x| \)[/tex].
5. Equation Pair: [tex]\( x = t + 4 \)[/tex] and [tex]\( y = -| t + 4 | \)[/tex]
- Substitute [tex]\( x = t + 4 \)[/tex] into [tex]\( y = -| t + 4 | \)[/tex]:
[tex]\[ y = -| t + 4 | = -| x | \][/tex]
- This satisfies [tex]\( y = -|x| \)[/tex]. Thus, this pair represents [tex]\( y = -|x| \)[/tex].
In conclusion, the parametric equations that represent [tex]\( y = -| x | \)[/tex] are:
- [tex]\( x = t^2 \)[/tex] and [tex]\( y = -| t^2 | \)[/tex]
- [tex]\( x = t + 4 \)[/tex] and [tex]\( y = -| t + 4 | \)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.